(untitled) (Revista Tempo e Argumento, 2016)
Abstract The main objective of this article was to analyze a report produced by the National Information Service (SNI), on March 28, 1978, during the campaign for Amnesty. The opening to consultation of the collections of the entities of control and repression of the military regime in Brazil, produced during the years 1964-1985, allowed access to thousands of documents and photographs. Keywords: Amnesty; Dictatorships and Dictators; Brazil – History – 1964-1985; Photographs. Original title: A campanha pela Anistia em imagens: Tempo Presente, fotografias e repressão política.